New insights into the development of maximal sprint speed in male youth - Meyers, R. W.; Oliver, J. L.; Hughes, M. G.; Lloyd, R. S.; Cronin, J. B. (Strength and Conditioning Journal, 2017)
Speed is a key aspect of youth physical development programs and commonly assessed during talent identification testing protocols, yet, little is understood about the factors that underpin the natural development of maximal speed throughout childhood and adolescence. This article reviews the anthropometric, kinematic, kinetic, and asymmetry variables that contribute to sprint performance, while examining the impact that growth and maturation may have on all facets of maximal sprint performance in boys. Clear guidance is provided on the practical applications for the strength and conditioning coach that should help in design of effective speed development programs for male youth.